Grain Yield and Total Protein Content of Organically Grown Oats–Vetch Mixtures Depending on Soil Type and Oats’ Cultivar - Katarzyna Pużyńska; Stanisław Pużyński; Agnieszka Synowiec; Jan Bocianowski; Andrzej Lepiarczyk (Agriculture, 2021)
The yield and quality of crop mixtures depend on natural and agrotechnical factors and their relationships. This research aimed to analyze the grain yield, its components and total protein content of the organically grown oat–vetch mixture on two different soils and depending on the oat cultivar. The three-year field experiment with two crop rotations was carried out. The experiment was set up in the southern Poland on two soils: Stagnic Luvisol (S.L.) and Haplic Cambisol (H.C.). One of four oat cultivars (‘Celer’, ‘Furman’, ‘Grajcar’ and ‘Kasztan’) was grown with the common vetch cv. ‘Hanka’. The results showed that the grain yield of mixtures was affected mainly by weather conditions. During the dry season, the share of vetch in the grain yield was 46% lower than in the season of regular rainfall. The share of vetch seeds in the mixture’s yield was ca. 21% higher when the mixtures were grown on the S.L. than the H.C. soil. The selection of oats’ cultivar for the mixture with vetch affected significantly the thousand seed mass and protein content in the vetch seeds, 46.2–50.4 g and 270–280 g kg−1, respectively. The mixture with Kasztan cultivar yielded the best and this oat cultivar seemed to be the most appropriate for organic conditions; however, in years with high variability of rainfall distribution its usefulness was less.